Evaluation of the Association between Body Mass Index and Severe Early Childhood Caries (S-ECC) among Children of Isfahan City - Afshin Mokhtarinia; Maryam Ebrahimian; Roya Foroughi Abari; Niloofar Norouz (Isfahan University of Medical Sciences, 2022)
The relationship between dental caries in children and abnormalities in their body mass index is still controversial. The aim of this study was to evaluate the association between Body Mass Index (BMI) and Severe Early Childhood Caries (SECC).Materials & Methods:In this case-control study, 150children with SECC (case group) and 150 caries-free kids for the control group were recruited from a number of Isfahan city's private clinics in the year 2019.Parameters including weight and height were measured, and BMI (kg/m2) was calculated. The subjects were categorized based on BMI adjusted for age and gender as: underweight (<5th percentile), healthy weight (5th to <85th percentile), overweight (85th to <95th percentile), and obesity (≥95th percentile). The data was analyzed by using Chi-squared, Fisher's exacttest, and Mann-Whitney by considering a significance level at 0.05.Results:There was a significant difference in the frequency of weight groups between the two groups of children without caries and with severe caries (p value = 0.007). There was a significant difference in the frequency of weight groups between boys and girls in the two groups of children (p value < 0.001). Frequency of weight groups in the age groups of 2, 3, 4 and 5 years there was a significant difference between the two groups of children (p value < 0.001). The mean body mass index in children with severe dental caries was significantly lower than children without caries (p value < 0.001).Conclusion:According to the findings, a majority of children with SECC were underweight compared to caries free children, suggesting SECC may adversely affect growth